Bicaval dual lumen cannula placement using transthoracic echocardiography in COVID-19 scenario: pearls and pitfalls. Issue 6 (15th June 2022) - Le, Ngoc Minh; Dang, Uyen The; Vu, Ha Viet; Nguyen, Hieu Lan
Abstract : A woman in her 50s who had been diagnosed with COVID-19 developed deep vein thrombosis in the left femoral vein extending into inferior vena cava (IVC). An IVC filter was placed to prevent fatal pulmonary embolism. Her respiratory failure subsequently deteriorated despite optimal mechanical ventilation and required venovenous extracorporeal membrane oxygenation (VV-ECMO) as a rescue therapy. Femoro-jugular VV-ECMO configuration was not suitable due to the IVC filter, hence a single-site venous cannulation using bicaval dual lumen (AvalonElite) cannula was selected. Placement of the Avalon cannula conventionally requires guidance by fluoroscopy or transoesophageal echocardiography, which were not feasible in COVID-19 patients. Hence, transthoracic echocardiography guidance was chosen. Guidewire looping into the right ventricle might lead to cannula malposition and imminent right ventricular rupture, but these could be detected by 'bending' sign. Transthoracic echocardiography could be a feasible guidance method for Avalon cannulation, nonetheless a thorough protocol should be followed to avoid cannula malposition during the procedure.